The effects of elastic tubing-based resistance training compared with conventional resistance training in patients with moderate chronic obstructive pulmonary disease: a randomized clinical trial - Cipulo Ramos, Ercy Mara [UNESP]; Toledo-Arruda, Alessandra Choqueta de [UNESP]; Fosco, Luciana Cristina [UNESP]; Bonfim, Rafaela [UNESP]; Bertolini, Giovana Navarro [UNESP]; Guarnier, Flavia Alessandra; Cecchini, Rubens; Pastre, Carlos Marcelo [UNESP]; Langer, Daniel; Gosselink, Rik; Ramos, Dionei [UNESP] (Sage Publications Ltd, 2014)
Objective: To investigate the effects of elastic tubing training compared with conventional resistance training on the improvement of functional exercise capacity, muscle strength, fat-free mass, and systemic inflammation in patients with chronic obstructive pulmonary disease.Design: A prospective, randomized, eight-week clinical trial.Setting: The study was conducted in a university-based, outpatient, physical therapy clinic.Subjects: A total of 49 patients with moderate chronic obstructive pulmonary disease.Interventions: Participants were randomly assigned to perform elastic tubing training or conventional resistance training three times per week for eight weeks.Main measures: The primary outcome measure was functional exercise capacity. The secondary outcome measures were peripheral muscle strength, health-related quality of life assessed by the Chronic Respiratory Disease Questionnaire (CRDQ), fat-free mass, and cytokine profile.Results: After eight weeks, the mean distance covered during six minutes increased by 73 meters (69) in the elastic tubing group and by 42 meters (+/- 59) in the conventional group (p < 0.05). The muscle strength and quality of life improved in both groups (P < 0.05), with no significant differences between the groups. There was a trend toward an improved fat-free mass in both groups (P = 0.05). After the first and last sessions, there was an increase in interleukin 1 (IL-1) and interleukin 10 (IL-10) in both groups, while tumour necrosis factor alpha (TNF-) was stimulated only in the conventional training group.Conclusion: Elastic tubing training had a greater effect on functional exercise capacity than conventional resistance training. Both interventions were equally effective in improving muscle strength and quality of life.
Keywords: Chronic obstructive pulmonary disease; muscle strength; rehabilitation; resistance training